STATSEARCH: a GCG-compatible program for assessing statistical significance during DNA and protein databank searches. - Mott, R; Kirkwood, T (1990)
We describe a program STATSEARCH which implements the method of Mott et al. (1989) for searching DNA and protein sequence databanks for statistically significant similarities to a given query sequence. STATSEARCH is written to run in conjunction with the GCG sequence analysis package.